(untitled) (Global Journal of Human-Social Science, 2016)
As an important part in academic writing meta discourse has got considerable attention in recent years Abstract plays an important role in academic writings and it reflects the main contents of the whole papers Based on the theory of metadiscourse and the classifications of Hyland this study compared the different frequency and usage of metadiscourse in mathematical and linguistic academic papers Two small abstracts corpora were compiled in this study including 30 mathematical and 30 linguistic abstracts of academic papers from Social Science Citation Index SSCI and Science Citation Index SCI journals The results showed that there appeared more metadiscourse in the abstracts of linguistic academic papers than mathematical academic papers Interactive meta discourse was adopted more than interactional metadiscourse in abstracts of the two disciplines In the use of interactive meta discourse both disciplines demonstrated the same trends in the frequencies of five sub-categories Regarding interactional metadiscourse hedges were the most frequently used meta discourse markers in linguistic academic papers while self mentions were most frequently used in mathematics It is suggested that more interactive meta discourse should be used in abstracts of both arts and science academic papers